Human right to language : communication access for deaf children - Siegel, Lawrence M., 1946- (Washington, D.C. : Gallaudet University Press, 2008)
"In 1982, the United States Supreme Court ruled that Amy Rowley, a deaf six-year-old, was not entitled to have a sign language interpreter in her public school classroom. Lawrence M. Siegel wholeheartedly disagrees with this decision in these pages. Instead, he contends that the United States Constitution should protect every deaf and hard of hearing child's right to communication and language as part of an individual's right to liberty. Siegel argues that when a deaf or hard of hearing child sits alone in a crowded classroom and is unable to access the rich and varied communication about her, the child is denied any chance of success in life."--Jacket.
The importance of communication and language -- Communication, language, and education -- The First Amendment : the broad right to express and receive information and ideas -- The First Amendment and freedom of association -- The importance of the First Amendment : protecting the extremes of speech -- Introduction to the Fourteenth Amendment -- Equal protection and the place of education in American society -- Equal protection and the right to communication and language -- The application of bilingual-education law and programs to deaf and hard of hearing students -- A proposal.
Includes bibliographical references and index.
Keywords: Deaf -- Legal status, laws, etc. -- United States; Hearing impaired -- Legal status, laws, etc. -- United States; Deaf children -- Education -- United States; Hearing impaired children -- Education -- United States; Deaf -- Means of communication; Deaf children -- Education; Deaf -- Legal status, laws, etc; Deaf -- Means of communication; Hearing impaired children -- Education; Hearing impaired -- Legal status, laws, etc; United States; USA; USA